Maize multi-omics reveal roles for autophagic recycling in proteome remodelling and lipid turnover. (December 2018) - McLoughlin, Fionn; Augustine, Robert; Marshall, Richard; Li, Faqiang; Kirkpatrick, Liam; Otegui, Marisa; Vierstra, Richard
Abstract The turnover of cytoplasmic material by autophagic encapsulation and delivery to vacuoles is essential for recycling cellular constituents, especially under nutrient-limiting conditions. To determine how cells/tissues rely on autophagy, we applied in-depth multi-omic analyses to study maize (Zea mays ) autophagy mutants grown under nitrogen-replete and -starvation conditions. Broad alterations in the leaf metabolome were evident in plants missing the core autophagy component ATG12, even in the absence of stress, particularly affecting products of lipid turnover and secondary metabolites, which were underpinned by substantial changes in the transcriptome and/or proteome. Cross-comparison of messenger RNA and protein abundances allowed for the identification of organelles, protein complexes and individual proteins targeted for selective autophagic clearance, and revealed several processes controlled by this catabolism. Collectively, we describe a facile multi-omic strategy to survey autophagic substrates, and show that autophagy has a remarkable influence in sculpting eukaryotic proteomes and membranes both before and during nutrient stress. It has been well established that nutrient starvation induces cell autophagy. Now, researchers present large-scale multi-omics analyses of maize autophagy mutants under nitrogen starvation, and show that autophagy could play more housekeeping roles in plants.